Tubridge flow diverter for the treatment of dissecting aneurysms in the middle cerebral artery - Duan, Yu; Huang, Guohui; Shen, Jun; Xu, Ziwei; Li, Zhuyu; Li, Jian; Dai, Dongwei (Frontiers in neurology, 2025)
The Tubridge flow diverter (TFD) has become a widely used device for reconstructing parent vessels and sealing complicated aneurysms in China. However, its application to managing distal small to medium-sized dissecting aneurysms has not been extensively investigated. This study aimed to evaluate the safety and effectiveness of the TFD and the factors affecting healing in patients with dissecting aneurysms in the middle cerebral artery (MCA). Patients with dissecting aneurysms in the MCA who were treated with the TFD from 2019 to 2023 were included. According to the O'Kelly-Marotta (OKM) scale, OKM grade A was defined as dense embolism, while OKM grades B to D were defined as non-dense embolism in this study. Clinical information, the degree of aneurysm occlusion, and clinical outcomes were retrospectively analyzed. A total of 25 patients with 25 MCA dissecting aneurysms were identified. The average age was 52.4 years (age range 20-76), with 5 patients (20%) experiencing subarachnoid hemorrhage. In total, 12 aneurysms were located in the M1 segment, 11 involved the M2 bifurcation, and two were in the M3 segment or above. The median aneurysm length was 17.3 mm (range 4.2-27), and the average width was 5.4 mm (range 2.3-7.6). A total of 12 cases had one or more branches in the MCA. Furthermore, four cases (16%) showed asymptomatic in-stent stenosis, and five cases (20%) had main branch injuries during the angiographic follow-up. A total of three patients experienced acute ischemic events, and one had not fully recovered during the follow-up. There were no deaths related to procedure complications. According to the single-factor analysis, the patients in the non-dense embolism group during the follow-up had more strong branches before the operation (χ = 9.001, = ). The TFD is a safe and effective flow diverter for distal dissecting MCA aneurysms. The aneurysms with strong branches were associated with a higher rate of non-dense embolism during the follow-up.